Protection of Precision Cut - Goat Liver Slices By Zea Mays Leaf Extracts From Hydrogen Peroxide Induced Oxidative Stress In Vitro - KIRUTHIKA BALASUBRAMANIAN; PALGHAT RAGHUNATHAN PADMA (International Journal of Pharma and Bio Sciences, 2012)
Plants play an indispensable part in the environment, especially as a medication to protect man from intrinsic and extrinsic ill effects imparted by stress agents. In tune with the search of antioxidant-rich plants, the leaves of Zea mays were analyzed for its antioxidant potential at three different stages of growth. The effect of the leaf extract on the oxidant stress induced in in vitro systems, which simulated in vivo conditions, were studied. The in vitro model used as a means to replace or minimize the use of live animals in experiments was goat liver slices. The aim of the present study was to assess the extent of oxidative stress, the activities and levels of antioxidants by the extracts of Zea mays in the presence and absence of oxidative stress. Our findings suggest that the hepatoprotection by Zea mays leaves against hydrogen peroxide induced oxidative stress could be due to its antioxidant property.